PENGARUH RATIO LEVERAGE TERHADAP RISIKO PASAR PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Savitri, Enni; Pramudya, Andra Lolija (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
The financial manager or chief financial officer (CFO) must be careful in making decisionsleverage. Leverage is the use of fixed costs in order to increase profits. Leverage There aretwo kinds of operating leverage and leverage spending. In the decision of operatingleverage, financial managers can use break-even analysis and the degree of operatingleverage (DOL) to determine how the effects of changes in sales volume to the change inoperating income. Leverage in spending decisions, financial managers can use indifferenceanalysis and degree of financial leverage (DFL) to determine how the effect of changes inoperating income to earnings per share (EPS). The combination of both the total leverage iscalled leverage. In making decisions leverage, financial managers is not enough to payattention to earnings that occur, but also should pay attention to risk. The risk is due to theoperating leverage, leverage spending, and total leverage each called business risk, the riskof spending.Keywords: degree of operating leverage, degree of financial leverage and market risk